Preparation method of solid-state battery

By using organic-inorganic composite solid electrolyte in solid-state batteries, and using the combination of polyvinylidene fluoride and modified nanotitanium dioxide, the problems of low ion conductivity and poor solid-solid interface stability of solid-state batteries are solved, and the cycle performance and rate performance of the battery are significantly improved.

CN119542560AActive Publication Date: 2025-02-28GUIZHOU HANGSHENG LITHIUM ENERGY TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411737278.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The low ionic conductivity of solid-state batteries and poor stability of solid-solid interfaces affect the rate performance and cycling performance of the battery.

Method used

Using an organic-inorganic composite solid electrolyte, a suspension is formed by combining polyvinylidene fluoride with modified nanotitanium dioxide, and uniformly coated on both sides of the cellulose film by scraping and coating, and a solid electrolyte is prepared after drying.

Benefits of technology

It improves the ionic conductivity and mechanical properties of solid-state batteries, and enhances the cycling and rate performance of the batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a solid-state battery, and belongs to the technical field of solid-state batteries. And assembling the battery in an argon glove box according to the sequence of the positive battery shell, the positive pole piece, the solid electrolyte, the negative pole piece, the foamed nickel and the negative battery shell to obtain the solid-state battery. Wherein the solid electrolyte is an organic-inorganic composite solid electrolyte, on one hand, the flexibility of an organic polymer is used for improving interface contact, on the other hand, an inorganic material can inhibit the growth of lithium dendrites, and the ionic conductivity of the solid electrolyte is improved; compared with common nano titanium dioxide, the prepared modified nano titanium dioxide has better compatibility with an organic polymer polyvinylidene fluoride, so that a solid-state battery has better cycle performance, and the modified nano titanium dioxide has important application value in the technical field of solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and specifically, relates to a method for preparing a solid-state battery. Background Art

[0002] In order to alleviate the energy crisis and protect the environment, various types of batteries have become necessities of life, and with the rapid development of new energy vehicles, the market demand for battery capacity and safety performance is getting higher and higher. Lithium-ion batteries are the most commonly used batteries on the market. Due to their high energy density, long cycle life, and good reliability, they have been widely developed and applied in the past decade.

[0003] Lithium-ion battery electrolytes are mostly organic carbonate solvents, such as ethylene carbonate, propylene carbonate, etc. However, safety issues such as leakage, fire, and explosion of lithium-ion batteries caused by traditional liquid electrolytes have seriously hindered the further development of lithium-ion batteries. Solid-state batteries do not contain liquid, and the gaps inside and on the interfaces of electrodes and diaphragms are not filled with liquid. The ion conduction path relies entirely on solid contact, which is a research hotspot in the current battery field. Compared with traditional liquid lithium-ion batteries, it has higher safety and energy density, which can theoretically exceed 500Wh / kg. Solid-state electrolytes are non-volatile and non-flammable, greatly improving battery safety.

[0004] Solid-state batteries are safe and have broad prospects. However, because there is no liquid in all-solid-state batteries, the gaps inside and at the interfaces of electrodes and separators are not filled with liquid, and the ion conduction path relies entirely on solid contact, resulting in low ion conductivity and poor solid-solid interface stability. These problems affect the battery's rate performance and cycle performance. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of solid-state battery technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a solid-state battery.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a solid-state battery comprises the following steps: The battery is assembled in an argon glove box in the order of positive electrode battery shell, positive electrode plate, solid electrolyte, negative electrode plate, nickel foam and negative electrode battery shell to obtain a solid-state battery.

[0007] Furthermore, the materials of the positive electrode battery shell and the negative electrode battery shell are both polypropylene.

[0008] Furthermore, the negative electrode plate material is lithium-aluminum alloy.

[0009] Furthermore, the positive electrode plate is prepared by the following steps: Polystyrene is dissolved in xylene to obtain a polymer solution, the polymer solution is mixed with lithium oxide, conductive carbon black (conductive agent) and polyvinylidene fluoride (binder) to obtain an active slurry, the active slurry is coated on the surface of aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing and slitting.

[0010] Furthermore, the mass ratio of the polystyrene, lithium oxide, conductive carbon black and polyvinylidene fluoride is 3:8:1:1.

[0011] Furthermore, the solid electrolyte is prepared by the following steps: Polyvinylidene fluoride (PVDF) and lithium bis(trifluoromethane) sulfonyl imide were added to N,N-dimethylformamide (DMF) and stirred at room temperature for 8 hours. Subsequently, modified nano-titanium dioxide was added and then magnetically stirred for 8 hours to fully disperse the modified nano-titanium dioxide to obtain a suspension. The suspension was evenly coated on both sides of a 30μm thick cellulose membrane by a doctor blade method, and finally dried in a forced air drying at 100°C for 6 hours to obtain a solid electrolyte.

[0012] Furthermore, the raw materials are calculated in parts by weight as follows: 40-60 parts of polyvinylidene fluoride, 4-6 parts of lithium bis(trifluoromethane)sulfonimide, and 5-15 parts of modified nano titanium dioxide.

[0013] The prepared solid electrolyte is an organic-inorganic composite solid electrolyte, wherein the organic material is polyvinylidene fluoride, which contains a strong electron-withdrawing group -CF, and is therefore highly stable to anions, can effectively increase the carrier concentration in the electrolyte system, and can also enhance the mechanical strength and electrochemical stability of the solid electrolyte; the inorganic material is nano-titanium dioxide, which is an inert inorganic filler, which can not only further improve the mechanical properties of the solid electrolyte, but also reduce the crystallinity of the organic material, thereby improving the ionic conductivity of the solid electrolyte.

[0014] Furthermore, the modified nano titanium dioxide is prepared by the following steps: S1. In a three-necked flask, sodium hydroxide solution (mass fraction 30%), anhydrous ethanol, nano titanium dioxide and lithium nitrate were added to a polytetrafluoroethylene reactor, the reaction temperature was controlled to be 180°C, the reaction was carried out for 8 hours, and after the reaction was completed, the mixture was washed with deionized water, and then treated under magnetic stirring for 24 hours, and the pH value was adjusted to 7 with hydrochloric acid solution, and then washed with deionized water again, filtered, and dried in a 100°C forced drying oven for 4 hours, and finally placed in a muffle furnace at 400°C and calcined for 2 hours to obtain surface lithiated titanium dioxide nanorods; the ratio of sodium hydroxide solution, anhydrous ethanol, nano titanium dioxide and lithium nitrate was 20mL:20mL:1g:6.6g; The morphology and composition of nano-titanium dioxide were changed by a hydrothermal method to obtain surface lithiated titanium dioxide nanorods; S2, mixing the surface lithiated titanium dioxide nanorods with the ethanol aqueous solution, adding them to a magnetic stirring device, adding a magnet, starting stirring, and dispersing for 30 minutes to uniformly disperse the surface lithiated titanium dioxide nanorods in the ethanol aqueous solution, evacuating the device, introducing N2 gas, and then adding vinyltrimethoxysilane, starting heating, setting 80°C, turning on condensation water, reacting for 4 hours, and after the reaction is completed, filtering, washing with ethanol, and then drying in a vacuum drying oven for 2 hours to obtain intermediate 1; the ratio of the surface lithiated titanium dioxide nanorods, the ethanol aqueous solution, and the vinyltrimethoxysilane is 1.0g:100mL:5.5g; The surface lithiated titanium dioxide nanorods react with vinyltrimethoxysilane to introduce a carbon-carbon double bond to obtain intermediate 1. The specific reaction process is as follows: ; S3, add mercaptoacetic acid, p-trifluoromethylaniline, dicyclohexylcarbodiimide (DCC, dehydrating agent) and N,N-dimethylformamide to a three-necked flask equipped with a stirring device, stir and mix well, place in a 40°C water bath, heat in a water bath for 6 hours, and complete the reaction. Filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 3:2), remove the eluent by rotary evaporation to obtain intermediate 2; the ratio of mercaptoacetic acid, p-trifluoromethylaniline, dicyclohexylcarbodiimide and N,N-dimethylformamide is 9.2g:16.1g:20.6g:150mL; Under the catalysis of DCC, the reaction conditions are relatively mild, and thioglycolic acid and trifluoromethylaniline undergo amidation reaction to obtain intermediate 2; the specific reaction process is as follows: ; S4. In a three-necked flask equipped with a stirring device, mix the intermediate 1 with N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes to make the intermediate 1 evenly dispersed, add the intermediate 2 and azobisisobutyronitrile (AIBN), set the reaction temperature to 75°C, keep the reaction for 6 hours, stir continuously during the reaction until the reaction is completed, distill under reduced pressure, wash, and freeze-dry to obtain modified nano titanium dioxide; the ratio of the amount of intermediate 1, N,N-dimethylformamide, intermediate 2, and azobisisobutyronitrile is 1g:100mL:6.5g:0.5g; Under the action of AIBN, the unsaturated carbon-carbon double bond on intermediate 1 and the thiol group on intermediate 2 undergo a thiol-ene click reaction to obtain modified nano-titanium dioxide; the specific reaction process is as follows: ; Nano-titanium dioxide is made into surface lithiated titanium dioxide nanorods by a hydrothermal method. After lithiation, the surface of the nano-titanium dioxide becomes rough, forming a particle layer with a certain ionic conductivity, which not only helps the interface bonding of inorganic materials and organic materials, but also improves the Lewis acid-base reaction. In addition, by further modifying the surface lithiated titanium dioxide nanorods to graft organic molecular chains and improve their interface effect, the compatibility of nano-titanium dioxide and organic material polyvinylidene fluoride can be enhanced, making the solid electrolyte more stable. In addition, the prepared modified nano-titanium dioxide also contains sulfur element and CF bond, wherein the electronegativity of sulfur element is low, and the bonding strength between sulfur and lithium ions is weak, which increases the concentration of free mobile lithium ions, and the radius of sulfur ions is larger than that of oxygen ions, thereby providing wider lattice pores for lithium ions to migrate, thereby enhancing the ionic conductivity of the solid electrolyte. Finally, the introduction of CF bond can further enhance the compatibility of nano-titanium dioxide and organic material polyvinylidene fluoride, so that the performance of the modified nano-titanium dioxide can be fully exerted, greatly enhancing the various properties of the solid electrolyte.

[0015] Beneficial effects of the present invention: 1. The electrolyte in the solid-state battery prepared by the present invention is an organic-inorganic composite solid electrolyte. On the one hand, the flexibility of the organic polymer is used to improve the interface contact, and on the other hand, the inorganic material can inhibit the growth of lithium dendrites and enhance the ionic conductivity of the solid electrolyte; 2. The modified nano-titanium dioxide obtained has better compatibility with the organic polymer polyvinylidene fluoride than ordinary nano-titanium dioxide, which makes the solid-state battery have better cycle performance; Therefore, the solid-state battery prepared by the present invention has good electrical properties, and the solid electrolyte ions in the solid-state battery have high conductivity and excellent mechanical properties, and has important application value in the field of solid-state battery technology. DETAILED DESCRIPTION

[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Embodiment 1

[0018] Preparation of modified nano-titanium dioxide: S1. In a three-necked flask, 20 mL of sodium hydroxide solution, 20 mL of anhydrous ethanol, 1 g of nano titanium dioxide and 6.6 g of lithium nitrate were added to a polytetrafluoroethylene reactor, the reaction temperature was controlled to be 180°C, the reaction was carried out for 8 hours, and after the reaction was completed, the mixture was washed with deionized water, and then treated under magnetic stirring for 24 hours, and the pH value was adjusted to 7 with a hydrochloric acid solution, washed with deionized water again, filtered, dried in a 100°C forced drying oven for 4 hours, and finally placed in a muffle furnace at 400°C and calcined for 2 hours to obtain surface lithiated titanium dioxide nanorods; S2, 1.0g of surface lithiated titanium dioxide nanorods was mixed with 100mL of ethanol aqueous solution, added to a magnetic stirring device, a magnet was added, stirring was started, and dispersion was carried out for 30min to make the surface lithiated titanium dioxide nanorods evenly dispersed in the ethanol aqueous solution, the device was evacuated, N2 gas was introduced, and 5.5g of vinyltrimethoxysilane was added, heating was started, set to 80°C, condensation water was turned on, and the reaction was carried out for 4h. After the reaction was completed, the intermediate 1 was filtered, washed with ethanol, and then dried in a vacuum drying oven for 2h to obtain the intermediate 1; S3, in a three-necked flask equipped with a stirring device, 9.2 g of thioglycolic acid, 16.1 g of p-trifluoromethylaniline, 20.6 g of dicyclohexylcarbodiimide and 150 mL of N,N-dimethylformamide were added, and after stirring and mixing, the mixture was placed in a water bath at 40°C and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 3:2), and the eluent was removed by rotary evaporation to obtain intermediate 2; S4. In a three-necked flask equipped with a stirring device, 1 g of intermediate 1 was mixed with 100 mL of N,N-dimethylformamide, and ultrasonically treated for 30 min to make the intermediate 1 evenly dispersed. 6.5 g of intermediate 2 and 0.5 g of azobisisobutyronitrile were added, and the reaction temperature was set to 75 ° C. The reaction was kept warm for 6 h. Stirring was continued during the reaction until the reaction was completed, and vacuum distillation, washing, and freeze-drying were performed to obtain modified nano titanium dioxide.

[0019] Embodiment 2

[0020] Preparation of modified nano-titanium dioxide: S1. In a three-necked flask, 40 mL of sodium hydroxide solution, 40 mL of anhydrous ethanol, 2 g of nano titanium dioxide and 13.2 g of lithium nitrate were added to a polytetrafluoroethylene reactor, the reaction temperature was controlled to be 180°C, the reaction was carried out for 8 hours, and after the reaction was completed, the mixture was washed with deionized water, and then treated under magnetic stirring for 24 hours, and the pH value was adjusted to 7 with a hydrochloric acid solution, washed with deionized water again, filtered, dried in a 100°C forced drying oven for 4 hours, and finally placed in a muffle furnace at 400°C and calcined for 2 hours to obtain surface lithiated titanium dioxide nanorods; S2, 2.0 g of surface lithiated titanium dioxide nanorods were mixed with 200 mL of ethanol aqueous solution, added to a magnetic stirring device, a magnet was added, stirring was started, and dispersion was performed for 30 min to uniformly disperse the surface lithiated titanium dioxide nanorods in the ethanol aqueous solution, the device was evacuated, N2 gas was introduced, and 11.0 g of vinyltrimethoxysilane was added, heating was started, the temperature was set to 80°C, condensation water was turned on, and the reaction was performed for 4 h. After the reaction was completed, the product was filtered, washed with ethanol, and dried in a vacuum drying oven for 2 h to obtain intermediate 1; S3, in a three-necked flask equipped with a stirring device, 18.4 g of thioglycolic acid, 32.2 g of p-trifluoromethylaniline, 41.2 g of dicyclohexylcarbodiimide and 300 mL of N,N-dimethylformamide were added, and after stirring and mixing, the mixture was placed in a water bath at 40°C and heated in a water bath for 6 h. After the reaction was completed, the mixture was filtered, and the solvent was removed by distillation under reduced pressure. The mixture was purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 3:2), and the eluent was removed by rotary evaporation to obtain intermediate 2; S4. In a three-necked flask equipped with a stirring device, 2 g of intermediate 1 was mixed with 200 mL of N,N-dimethylformamide, and ultrasonic treatment was performed for 30 min to make the intermediate 1 evenly dispersed. 13.0 g of intermediate 2 and 1 g of azobisisobutyronitrile were added, and the reaction temperature was set to 75 ° C. The reaction was kept warm for 6 h. Stirring was continued during the reaction until the reaction was completed, and vacuum distillation, washing, and freeze-drying were performed to obtain modified nano titanium dioxide.

[0021] Embodiment 3

[0022] Preparation of solid electrolyte: 40 g of polyvinylidene fluoride and 4 g of lithium bis(trifluoromethane)sulfonyl imide were added to 150 mL of N,N-dimethylformamide and stirred at room temperature for 8 h. Subsequently, 5 g of the modified nano-titanium dioxide prepared in Example 1 was added, and then magnetic stirring was performed for 8 h to fully disperse the modified nano-titanium dioxide to obtain a suspension. The suspension was evenly coated on both sides of a 30 μm thick cellulose film by a doctor blade method, and finally dried in a forced air drying at 100° C. for 6 h to obtain a solid electrolyte.

[0023] Embodiment 4

[0024] Preparation of solid electrolyte: 50 g of polyvinylidene fluoride and 5 g of lithium bis(trifluoromethane)sulfonyl imide were added to 150 mL of N,N-dimethylformamide and stirred at room temperature for 8 h. Subsequently, 10 g of the modified nano-titanium dioxide prepared in Example 2 was added, and then magnetic stirring was performed for 8 h to fully disperse the modified nano-titanium dioxide to obtain a suspension. The suspension was evenly coated on both sides of a 30 μm thick cellulose film by a doctor blade method, and finally dried in a forced air drying at 100° C. for 6 h to obtain a solid electrolyte.

[0025] Embodiment 5

[0026] Preparation of solid electrolyte: 60 g of polyvinylidene fluoride and 6 g of lithium bis(trifluoromethane)sulfonyl imide were added to 150 mL of N,N-dimethylformamide and stirred at room temperature for 8 h. Subsequently, 15 g of the modified nano-titanium dioxide prepared in Example 2 was added, and then magnetic stirring was performed for 8 h to fully disperse the modified nano-titanium dioxide to obtain a suspension. The suspension was evenly coated on both sides of a 30 μm thick cellulose film by a doctor blade method, and finally dried in a forced air drying at 100° C. for 6 h to obtain a solid electrolyte.

[0027] Embodiment 6

[0028] Preparation of positive electrode sheet: 3 g of polystyrene was dissolved in 100 mL of xylene to obtain a polymer solution, and the polymer solution was mixed with 8 g of lithium oxide, 1 g of conductive carbon black and 1 g of polyvinylidene fluoride (binder) to obtain an active slurry, and the active slurry was coated on the surface of aluminum foil, and the positive electrode sheet was obtained by drying, cold pressing and slitting.

[0029] Embodiment 7

[0030] Preparation of solid-state batteries: Assembling the battery in an argon glove box in the order of a positive electrode battery shell, a positive electrode plate prepared in Example 6, a solid electrolyte prepared in Example 3, a negative electrode plate, nickel foam, and a negative electrode battery shell to obtain a solid-state battery; The materials of the positive battery shell and the negative battery shell are both polypropylene; the material of the negative electrode plate is lithium aluminum alloy.

[0031] Embodiment 8

[0032] Preparation of solid-state batteries: Assembling the battery in an argon glove box in the order of a positive electrode battery shell, a positive electrode plate prepared in Example 6, a solid electrolyte prepared in Example 4, a negative electrode plate, nickel foam, and a negative electrode battery shell to obtain a solid-state battery; The materials of the positive battery shell and the negative battery shell are both polypropylene; the material of the negative electrode plate is lithium aluminum alloy.

[0033] Embodiment 9

[0034] Preparation of solid-state batteries: Assembling the battery in an argon glove box in the order of a positive electrode battery shell, a positive electrode plate prepared in Example 6, a solid electrolyte prepared in Example 5, a negative electrode plate, nickel foam, and a negative electrode battery shell to obtain a solid-state battery; The materials of the positive battery shell and the negative battery shell are both polypropylene; the material of the negative electrode plate is lithium aluminum alloy.

[0035] Comparative Example 1 The modified nano titanium dioxide in Example 5 was replaced by ordinary nano titanium dioxide of the same mass, and the remaining steps were the same as those in Example 5 to prepare a solid electrolyte.

[0036] Comparative Example 2 The solid electrolyte prepared in Comparative Example 1 was used to replace the solid electrolyte in Example 9, and the remaining steps were the same as those in Example 9 to prepare a solid-state battery.

[0037] The following performance tests were conducted on Examples 3, 4, 5 and Comparative Example 1 with different test standards: The tensile properties were measured using the Meters MTSCMT8535 tensile tester, with the test sample cut into a dumbbell shape with a length of 20 mm, a width of 5 mm, a thickness of approximately 40 μm, and a frequency of 20 Hz; Electrochemical impedance spectroscopy was used to measure the ionic conductivity of solid electrolytes; The measured results are shown in Table 1: .

[0038] The electrical performance tests were conducted on Example 7, Example 8, Example 9 and Comparative Example 2, and the results are shown in Table 2: .

[0039] It can be seen from the above table that the solid-state battery prepared in the embodiment of the present invention has high ion conductivity and good cycle performance, and the solid electrolyte in the solid-state battery has excellent mechanical properties, and has important application value in the field of solid-state battery technology.

[0040] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0041] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a solid-state battery, characterized in that: The following steps are involved: The battery is assembled in an argon glove box in the order of positive electrode battery shell, positive electrode plate, solid electrolyte, negative electrode plate, nickel foam and negative electrode battery shell to obtain a solid-state battery.

2. The method for preparing a solid-state battery according to claim 1, characterized in that: The solid electrolyte is prepared by the following steps: Polyvinylidene fluoride and lithium bis(trifluoromethane)sulfonyl imide are added to N,N-dimethylformamide and stirred at room temperature, modified nano titanium dioxide is added, and then stirred to obtain a suspension; the suspension is evenly coated on both sides of a cellulose membrane by a doctor blade method, and dried to obtain a solid electrolyte.

3. The method for preparing a solid-state battery according to claim 2, characterized in that: The modified nano titanium dioxide is prepared by the following steps: S1, adding sodium hydroxide solution, anhydrous ethanol, nano titanium dioxide and lithium nitrate into a reaction kettle, reacting at 180°C for 8 hours, washing, stirring under magnetic stirring for 24 hours, adjusting the pH value to 7, washing again, filtering, drying, and finally placing in a muffle furnace at 400°C for calcining for 2 hours to obtain surface lithiated titanium dioxide nanorods; S2, mixing the surface lithiated titanium dioxide nanorods with ethanol aqueous solution, adding them to a magnetic stirring device, adding a magnet, starting stirring, dispersing for 30 minutes, evacuating the device, introducing N2 gas, adding vinyltrimethoxysilane, starting heating, setting the temperature to 80°C, turning on condensation water, reacting for 4 hours, and after the reaction is complete, filtering, washing, and drying to obtain intermediate 1; S3, mixing thioglycolic acid, p-trifluoromethylaniline, dicyclohexylcarbodiimide and N,N-dimethylformamide, placing in a 40°C water bath, heating in the water bath for 6 hours, the reaction is completed, filtering, vacuum distillation, column chromatography purification, rotary evaporation, to obtain intermediate 2; S4. Mix the intermediate 1 with N,N-dimethylformamide, perform ultrasonic treatment for 30 minutes to make the intermediate 1 evenly dispersed, add the intermediate 2 and azobisisobutyronitrile, react at 75°C for 6 hours, stir continuously during the reaction, and after the reaction is completed, perform vacuum distillation, wash, and freeze-dry to obtain modified nano titanium dioxide.

4. The method for preparing a solid-state battery according to claim 3, characterized in that: In step S1, the ratio of the amount of sodium hydroxide solution, anhydrous ethanol, nano titanium dioxide and lithium nitrate is 20 mL: 20 mL: 1 g: 6.6 g.

5. The method for preparing a solid-state battery according to claim 3, characterized in that: In step S2, the ratio of the surface lithiated titanium dioxide nanorods, the ethanol aqueous solution, and vinyltrimethoxysilane is 1.0 g:100 mL:5.5 g.

6. The method for preparing a solid-state battery according to claim 3, characterized in that: In step S3, the ratio of the amount of thioglycolic acid, p-trifluoromethylaniline, dicyclohexylcarbodiimide, and N,N-dimethylformamide is 9.2 g:16.1 g:20.6 g:150 mL.

7. The method for preparing a solid-state battery according to claim 3, characterized in that: In step S4, the ratio of the amount of intermediate 1, N,N-dimethylformamide, intermediate 2, and azobisisobutyronitrile is 1 g:100 mL:6.5 g:0.5 g.

8. The method for preparing a solid-state battery according to claim 2, characterized in that: The raw materials are calculated in parts by weight as follows: 40-60 parts of polyvinylidene fluoride, 4-6 parts of lithium bis(trifluoromethane)sulfonimide, and 5-15 parts of modified nano titanium dioxide.

9. The method for preparing a solid-state battery according to claim 1, characterized in that: The positive electrode sheet is prepared by the following steps: Polystyrene is dissolved in xylene to obtain a polymer solution, the polymer solution is mixed with lithium oxide, conductive carbon black and polyvinylidene fluoride to obtain an active slurry, the active slurry is coated on the surface of aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing and slitting.

10. The method for preparing a solid-state battery according to claim 9, characterized in that: The mass ratio of the polystyrene, lithium oxide, conductive carbon black and polyvinylidene fluoride is 3:8:1:1.

Citation Information

Patent Citations

  • Inorganic nano particle filler for solid state electrolyte and preparation method of inorganic nano particle filler

    CN107134587A

  • Modification method of polymer solid polyelectrolyte

    CN112864469A

  • Preparation method and application of ionic conductive frame enhanced solid electrolyte

    CN117936885A

  • PEO-based composite electrolyte membrane, preparation method thereof and all-solid-state battery

    CN118136944A